Leading and managing change : raising the bar of the Philippine population management program - Joven, Maria Velen A. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2022)
The study was suggestive of crystallizing a collective experience of local population managers in applying leadership and management concepts and good practices to appropriately and intentionally leverage leadership and management skills required to ensure efficiency, effectiveness, adaptability, and sustainability of investments in population and development. It is qualitative in its approach and employed an interpretative phenomenological approach in analyzing text data from thirteen receptive population and development managers during the hard- pressed and busiest time of COVID-19 pandemic. The findings of the study led to an adaptable model on leadership and management to illustrate the institutional support given by the local government to deliver a basic service on population and development and best practices on leadership and management necessary to scale-up the implementation of a population program at the local government. The study captures a wholistic interplay of all essential schemes to institutionalize a strong population management program complemented by empowered and enabling leadership engagement, program management and best practices relevantly and timely needed to sustain an outcome-based local population program in Region 1. The results and findings of the study have major and significant mplications for a changing and transformative leadership and anagement in the area of population, health and development. opulation and demographic issues remain today as difficult or likely a sinor concern. Equally important is linking the population agenda to ustainable development especially at the local level. Flexible mechanisms ach as funding, policy support, organizational structure and appropriate d applicable leadership and management practices accrue to local mographic dividend and development benefits.
References: pages 136-150.
CHED-La Union
Keywords: Population -- Management